The Contributions of Business Intelligence and Big Data to Public Healthcare in South Africa - (:unkn) unknown (My University, 2024)
The public health sector in South Africa generates massive data and it caters to about 71% of the population. The introduction of electronic medical records has made this data difficult to process. The adoption of business intelligence and big data became a solution for processing and analysing this increased data. The research aimed to provide an understanding of the existing contributions of business intelligence and big data in public healthcare in South Africa. Our research question is what are the benefits and challenges of adopting the use of business intelligence and big data in healthcare in South Africa? A systematic search was conducted in seven electronic databases (EbscoHost, Science Direct, ProQuest, Scopus, Sabinet, SpringerLink, and Google Scholar). The inclusion criteria were journal papers, books, book chapters, reviews, and conference proceedings reporting on big data, big data analytics, and business intelligence in South African healthcare. 22 articles were analysed for the study. The findings revealed that business intelligence and big data help by shortening diagnostic tests (through early diagnosis), reducing risks in healthcare services, reducing hospital costs, and improving patients’ health. However, there are issues like privacy, security, and poor data quality that need attention. The study contributes to the body of knowledge on healthcare informatics. Our study provides evidence for practitioners, policymakers, scholars, and technology advocates to advance the adoption and use of big data and business intelligence in the public healthcare system in developing countries. Our research contributes to sustainable development goal 3 (target 3.d).
Keywords: African Research